Adoption of Cocoa Certification Scheme and Farmer’s Technical Efficiency in Cameroon: A Double Bootstrap Procedure - Longang, Saubaber, Gamo; Boris, Soh, Wenda; Bergaly, Kamdem, Cyrile; Tamwo, Severin (My University, 2023)
In a bid to promote the adoption of certification schemes in the cocoa subsector, this study used data collected from 100 cocoa farmers applied on the two-stage double bootstrap data envelopment analysis (DEA) procedure to estimate the bias-corrected technical efficiency scores of cocoa producers with respect to the level of adoption of the Rainforest Alliance/UTZ cocoa certification scheme in the Centre region of Cameroon. The result indicates that yields per hectare remain low for cocoa farmers but is highest for partial adopters, followed by complete adopters and non-adopters; inefficiency remains rampant amongst cocoa farmers but declines as one moves from non-adoption to partial and then complete adoption. However, partial adoption appears to be more favourable for technical efficiency relative to complete adoption in the short run. Moreover, inefficiency is highest for nonadopters as their respective ages and the year of their experience increase. Likewise, non-adopters and partial adopters with secondary or higher level of schooling tend to be less efficient than complete adopters with similar level of schooling. This study therefore shows that the level of adoption of certification schemes matter for farmers’ technical efficiency. Hence certification bodies and agricultural extension programs should promote the adoption of certification schemes and encourage farmers to adopt the certification norms progressively and move from nonadoption to partial adoption in the short run and then to complete adoption in the long run.
Keywords: Cameroon; Certification adoption; Cocoa; Double-bootstrapped DEA procedure; Technical efficiency